SISTEMMINA-HORTIKULTUR BUDIDAYA LELEDUMBO DALAM KOLAM TERPAL-BATAKO DAN TANAMAN SAYURAN PADA POTVERTIKAL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
"Sistem Mina-Hortiku/tur" is an integrated fish/aqua-horticulture system. The system was applied on the cultivation of catfish and vegetable plants, which used environmentally friendly and sustainable technologies. The applied technologies were based on the research, which were consisted of the catfish cultured in palko (terpal-batako) ponds and the using of the ponds water as plants fertiliser and the vegetable plants (mustard and salad) cultured in vertical pots. The trial application of the system confirmed that the palko ponds were easy to make at various size. In addition, it also can be moved and rebuilt easily.The organic and inorganic contents of the catfish pond water could be used as a source of plants fertilizer. The vertical pot was constructed next to the ponds so that the pond water could be readily applied as the fertilizer. This fish/aqua-horticulture system has a potency to be implemented in household scale as well as industrial scale.